Removal of humic substances from peat swamp runoff using coconut copra and its application - Ean, Terri Lee Zhuan (Universiti Malaysia Sarawak (UNIMAS), 2016)
Humic substances are organic rich macromolecules commonly found in water tainted by peat swamp runoff. They cause undesirable colour and odour and pose significant impact on the treatability of water. The presence of humic substances in aquatic environment is a challenge to many water treatment authorities. They are the precursors to formation of carcinogenic compounds as they react with chlorine residues present in water after treatment processes. Conventional water treatment technique using coagulation and flocculation has good removal efficiency but the process generates resultant sludge which is discarded later. Often time, the amount of coagulant used is overdosed to affirm its removal efficiency, overlooking the potential hazards to human and environment health. On the other hand, humic substances have valuable agronomic values to farmers. Humic substances have been found to be soil enhancer and plant growth promoter. Hence, this study attempts to link the contradicting characteristics of humic substances to water treatment authorities and agriculture practitioners. Biosorption is gaining attention due to the abundance of agricultural biomasses, environmental friendly and economical sustainable, promoting green technology. Application of biosorbent serves to minimize the usage of alum in water treatment process. In this study, the potential of indigenous agricultural wastes in humic adsorption was evaluated. Coconut copra outperformed other biomasses studied; attaining 44.17% removal in its untreated state. It was further modified chemically to enhance its adsorption efficiency, where the chemical and morphological changes were confirmed using FTIR and SEM. Coconut copra was refluxed with distilled water and subsequently treated with citric acid. The treatment process is rather mild and environmental friendly. Upon modification, coconut copra experienced reduction in lignin content, glycosidic linkages and C–H stretching but enhanced C=O groups. Electrostatic, hydrophobic, hydrophilic and hydrogen bonding were anticipated in the adsorption of humic substances onto modified coconut copra. The chemical modification and water treatment condition were optimized at one-factor-at-a-time approach at laboratory setting. Coconut copra was refluxed using distilled water for 1 hour at 100 ºC, followed by agitation with 0.5 M citric acid for 1 hour at room temperature. A total of 1 g of modified coconut copra washed to pH 3 was agitated for 15 iv min recorded removal percentage above 95%. Adsorption isotherm studies were performed using Langmuir, Freundlich, Temkin and Dubinin-Radushkevich models with humic acid standard. The adsorption of humic acid using modified coconut copra is a favourable physical process with qmax of 232.56 mg/g. Response surface methodology was conducted based on inscribed central composite design to optimize the adsorption of humic substances for up scaling purpose. Experimental 86.54% humic removal was obtained when 4.56 g modified coconut copra is agitated in 100 mL peat swamp runoff at 56.8 ºC for 42.9 min. The experimental response acquired (based on the modelled optimum conditions. The recycling of humic fortified coconut copra to poultries feed is potentially viable. Humic solution was proven to be able to be germination promoter and plant growth enhancer with reference to mung beans.